1998
DOI: 10.1590/s0074-02761998000300022
|View full text |Cite
|
Sign up to set email alerts
|

HIV Specific Humoral Immune Response in Rio de Janeiro, Brazil

Abstract: Efforts to characterize HIV-1 polymorphism and anti-HIV immune response are being made in areas where anti-HIV/AIDS vaccines are to be employed. Anti-HIV-1 humoral immune response is being studied in infected individuals resident in Rio de Janeiro, in distinct cohorts involving recent seroconvertors, pregnant women or intravenous drug users (IDU). Comparative analyses of specificity of antibody response towards epitopes important for anti-HIV-1 immune response indicate quantitative differences between cohorts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…More studies are needed to establish if the identification of the B%% HIV-1 variant is important in anti HIV-1 therapy or choice of anti-HIV-1 vaccines. Data available up to now indicate that in regard to viral neutralization the B%% variant of the HIV-1 B subtype shows similar susceptibility to neutralizing antibodies (Bongertz et al, 1998b), even though differences in antibody binding assays are observed (Cheingsong Popov et al, 1994;Pau et al, 1994;Bongertz et al, 1998a). As to the extensive cross-reactivity observed between genotypically distinct HIV-1 subtypes, apart from the similarity of the V3 peptides used, a possible explanation could be in vivo variations of V1/V2 sequences affecting response to a given V3 sequence (Rencher and Hurwitz, 1997) and number and position of glycosylation sites (Groenink et al, 1993;Back et al, 1994) which would reflect in in vitro differences of response against synthetic peptides, thereby diminishing the usefulness of serotyping assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are needed to establish if the identification of the B%% HIV-1 variant is important in anti HIV-1 therapy or choice of anti-HIV-1 vaccines. Data available up to now indicate that in regard to viral neutralization the B%% variant of the HIV-1 B subtype shows similar susceptibility to neutralizing antibodies (Bongertz et al, 1998b), even though differences in antibody binding assays are observed (Cheingsong Popov et al, 1994;Pau et al, 1994;Bongertz et al, 1998a). As to the extensive cross-reactivity observed between genotypically distinct HIV-1 subtypes, apart from the similarity of the V3 peptides used, a possible explanation could be in vivo variations of V1/V2 sequences affecting response to a given V3 sequence (Rencher and Hurwitz, 1997) and number and position of glycosylation sites (Groenink et al, 1993;Back et al, 1994) which would reflect in in vitro differences of response against synthetic peptides, thereby diminishing the usefulness of serotyping assays.…”
Section: Discussionmentioning
confidence: 99%
“…However, results have indicated that the use of seroreactivity data for typing HIV-1 is not indicated when molecular subtypes are to be iden-tified. Serotyping of HIV-1 genotypes circulating in Brazil has been attempted with partial result: although distinction of the classical B (GPG) from the B%% variant (GWG) has been possible in the majority of cases (Cheingsong Popov et al, 1994;Pau et al, 1994;Hendry et al, 1996;Bongertz et al, 1998a), distinction of B and F HIV-1 subtypes has not been conclusive by any serological method attempted up to now (Casseb et al, 1997;Hendry et al, 1997;Bongertz et al, 1998a). In this study, humoral anti-HIV-1 responses were evaluated using synthetic peptides corresponding to epitopes known to induce HIV-1 neutralizing antibodies and therefore possibly of importance for control of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Following experimental HIV vaccination in Brazil, anti-HIV-1 immune response was the strongest in intravenous drug users (IDU) group and the weakest in pregnant women. A comparative analysis between pregnant women cohorts from different regions of Brazil indicated an even lower response for the southern population (Bongertz et al 1998). So, unrecognized HIV infection just prior or during pregnancy may result in higher rates of prenatal transmission (Patterson et al 2007).…”
Section: Potential Causes and Effectors Of The Length Of The Wpmentioning
confidence: 99%
“…The Brazilian B 00 variant can be fairly well distinguished from the classical Bsubtype by binding to the corresponding synthetic B 00 -or B-V3 peptides [32,33]. The neutralization susceptibility of B 00 -variant HIV-1 isolates towards B-or F-subtype plasma indicates that epitopes different from the V3 must be important for inducing antibodies capable of cross-neutralization.…”
Section: Discussionmentioning
confidence: 99%